High-strength ceramsite and preparation method thereof

By using secondary aluminum ash, electroplating sludge and construction sludge as raw materials, combined with the optimized preparation process, the problems of uneven foaming and insufficient strength of the ceramic granules were solved, and high-strength, uniform foaming ceramic granules were prepared, realizing the The dual goals of improving the performance of ceramite and the resource utilization of solid waste.

CN119285259APending Publication Date: 2025-01-10YUYUAN NINGHAI ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411192860.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing ceramic preparation methods affect the quality and application effect of ceramic grains.

Method used

Using secondary aluminum ash, electroplating sludge and construction sludge as raw materials, the production process with higher strength and more uniformity is prepared by optimizing the preparation process, including precise ratio, water spray stirring, pressing, air drying and three-stage high-temperature sintering. Foamed ceramic granules.

Benefits of technology

It improves the performance and quality of ceramite, promotes the resource utilization of solid waste, achieves the dual goals of environmental protection and economic benefits, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to high-strength ceramsite and a preparation method thereof. The high-strength ceramsite is prepared from the following raw materials in parts by weight: 30 to 60 parts of secondary aluminum ash, 10 to 40 parts of electroplating sludge and 10 to 60 parts of building sludge, the preparation method comprises the following steps: uniformly mixing the secondary aluminum ash, the electroplating sludge and the building sludge, spraying water, continuously stirring, pressing, air-drying, sintering at high temperature, and naturally cooling. Secondary aluminum ash, electroplating sludge and building sludge are used as raw materials, an optimized preparation process is combined, a ceramsite product which is higher in strength and more uniform in foaming is produced, the obtained ceramsite product not only has better performance and quality, but also can further promote the resource utilization process of solid waste, and the production cost is reduced. And the dual goals of environmental protection and economic benefit are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to high-strength ceramsite and a preparation method thereof. Background Art

[0002] Solid waste refers to solid and semi-solid waste materials generated by humans in production, consumption, life and other activities, mainly including solid particles, garbage, slag, sludge, discarded products, etc., which can be roughly divided into three categories: industrial waste, agricultural waste and domestic waste. With the acceleration of urbanization, more solid waste is generated, such as secondary aluminum ash, sludge, etc. If these wastes are not handled properly, they will not only occupy a large amount of land resources, but also may have serious impacts on the environment and human health. Therefore, how to effectively utilize these wastes and transform them into valuable resources has become a hot topic in current research.

[0003] In the technology of waste resource utilization, the preparation of ceramsite has attracted much attention due to its unique advantages. Ceramsite is a lightweight aggregate produced by foaming in a rotary kiln. It has a hard outer shell on the surface. This outer shell is ceramic or glazed, which has the function of water-proofing and air-retaining, and gives ceramsite a higher strength. It can be used to replace gravel and pebbles in concrete in the field of building materials. At the same time, the interior of ceramsite is composed of fine honeycomb micropores. These micropores are all closed and are formed by the gas being wrapped in the shell. This is also the main reason why ceramsite is light. As a man-made lightweight aggregate, ceramsite has a wide range of applications in construction, water treatment, gardening and other fields due to its light weight, porosity, high strength and good thermal insulation. In recent years, researchers have been constantly exploring methods to prepare ceramsite from solid waste in order to maximize resource utilization and protect the environment.

[0004] A Chinese patent document (publication number CN116606123A) proposes a method for preparing ceramsite by in-situ foaming of secondary aluminum ash, using grate bottom ash, secondary aluminum ash and fly ash from municipal solid waste incineration as raw materials, and preparing high-strength and lightweight ceramsite by in-situ foaming technology, which can improve the foaming performance and compressive strength of ceramsite to a certain extent, and then further improve the uniformity of ceramsite pores by adding a composite foam stabilizer, and prepare high-strength and light-weight ideal ceramsite. However, the preparation method of ceramsite may face problems such as uneven foaming and unsatisfactory ceramsite strength during the preparation process, which affects the quality and application effect of ceramsite. Summary of the invention

[0005] The purpose of the present invention is to solve the above technical problems, use secondary aluminum ash, electroplating sludge and construction sludge as raw materials, and combine them with optimized preparation technology to produce ceramsite products with higher strength and more uniform foaming.

[0006] The high-strength ceramsite in the technical solution of the present invention comprises the following raw materials in parts by weight: 30 to 60 parts of secondary aluminum ash, 10 to 40 parts of electroplating sludge and 10 to 60 parts of construction sludge.

[0007] The present invention uses secondary aluminum ash, electroplating sludge and construction sludge as raw materials to prepare high-strength ceramsite. Al2O3 in the secondary aluminum ash can provide good thermal stability, and fluxing agents such as CaO in the electroplating sludge and construction sludge can reduce the eutectic temperature, realize sintering at a lower temperature, optimize the process flow, expand the source of raw materials, and more effectively utilize the useful components in solid waste.

[0008] Furthermore, the secondary aluminum ash includes the following components in weight percentage: 5-10% SiO2, 5-10% Al2O3, 1-5% Fe2O3, 1-5% CaO, and 3-8% MgO.

[0009] Furthermore, the secondary aluminum ash also includes 0.10-0.40% Cu, 0.01-0.06% Ni, 0.05-0.20% Cr, 0.10-0.50% Zn, and 0.03-0.08% Pb.

[0010] Furthermore, the electroplating sludge includes the following components in weight percentage: 1-5% SiO2, 3-8% Al2O3, 8-15% Fe2O3, 20-28% CaO, and 5-10% MgO.

[0011] Furthermore, the electroplating sludge also includes 0.05-0.20% Cu, 0.10-0.20% Ni, 0.15-0.25% Cr, 0.30-0.80% Zn, and 0.01-0.03% Pb.

[0012] Furthermore, the water content of the electroplating sludge is 60-70%.

[0013] Furthermore, the construction sludge comprises the following components in weight percentage: 50-60% SiO2, 10-20% Al2O3, 5-10% Fe2O3, and 2-5% MgO.

[0014] Furthermore, the construction sludge also includes 0.002-0.006% Cu, 0.003-0.008% Ni, 0.01-0.03% Cr, 0.01-0.05% Zn, and 0.001-0.005% Pb.

[0015] Furthermore, the water content of construction sludge is 30-40%.

[0016] Furthermore, the particle sizes of secondary aluminum ash, electroplating sludge and construction sludge are all less than 150 μm.

[0017] Furthermore, the content of heavy metals in the above-mentioned high-strength ceramsite is: Cu 0.02-0.05%, Ni 0.001-0.005%, Cr 0.003-0.014%, Zn 0.03-0.17%, Pb 0.001-0.006%.

[0018] The present invention also provides a method for preparing the high-strength ceramsite, comprising the following steps: evenly mixing secondary aluminum ash, electroplating sludge and construction sludge, spraying water and continuously stirring, pressing and then air-drying, and naturally cooling after high-temperature sintering.

[0019] Through precise proportions combined with optimized preparation technology, we can produce expanded clay products with higher strength and more uniform foaming, which not only helps to improve the performance and quality of expanded clay, but also further promotes the resource utilization of solid waste and achieves the dual goals of environmental protection and economic benefits.

[0020] Furthermore, the pressing pressure is 2 to 5 MPa.

[0021] Furthermore, three-stage heat preservation sintering is adopted during high temperature sintering.

[0022] Furthermore, the high temperature sintering is firstly kept at 750-800°C for 20-30 minutes, then kept at 800-1150°C for 10-20 minutes, and finally kept at 1150-1200°C for 5-10 minutes.

[0023] Preferably, electroplating sludge and construction sludge are dried and ground before use.

[0024] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0025] (1) The present invention uses secondary aluminum ash, electroplating sludge and construction sludge as raw materials, combined with an optimized preparation process, to produce ceramsite products with higher strength and more uniform foaming;

[0026] (2) Using secondary aluminum ash, electroplating sludge and construction sludge as raw materials expands the source of raw materials and more effectively utilizes the useful components in solid waste;

[0027] (3) The obtained ceramsite products not only have good performance and quality, but also can further promote the resource utilization of solid waste and achieve the dual goals of environmental protection and economic benefits;

[0028] (4) The preparation method of high-strength expanded clay is simple and efficient, and is suitable for large-scale industrial application. DETAILED DESCRIPTION

[0029] The technical scheme of the present invention is further described below by specific embodiments. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended to be used for specific limitations of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0030] The electroplating sludge used in the following embodiments and comparative examples includes the following components in weight percentage: 1.11% SiO2, 4.66% Al2O3, 10.71% Fe2O3, 23.41% CaO, 8.87% MgO, 0.11% Cu, 0.14% Ni, 0.20% Cr, 0.56% Zn, 0.01% Pb, and the moisture content is 64.9%; the construction sludge includes the following components in weight percentage: 55.26% SiO2, 16.06% Al2O3, 8.4% Fe2O3, 4.24% MgO, 0.005% Cu, 0.006% Ni, 0.015% Cr, 0.032% Zn, 0.004% Pb, and the moisture content is 38.6%.

[0031] Example 1

[0032] The preparation method of the high-strength ceramsite of the present embodiment comprises the following steps:

[0033] (1) secondary aluminum ash, electroplating sludge and construction sludge after drying and grinding are sieved to make their particle sizes less than 150 μm, and then 50 parts of secondary aluminum ash, 40 parts of electroplating sludge and 10 parts of construction sludge are mixed evenly, sprayed with water and continuously stirred, and pressed into cylindrical blanks by a manual press at a pressure of 3 MPa, and naturally air-dried for 24 hours; the secondary aluminum ash includes the following components in weight percentage: 6.79% SiO2, 8.15% Al2O3, 2.07% Fe2O3, 2.07% CaO, 4.81% MgO, 0.29% Cu, 0.04% Ni, 0.14% Cr, 0.41% Zn, and 0.06% Pb;

[0034] (2) The naturally air-dried cylindrical blank is first kept at 760°C for 30 min, then kept at 1000°C for 20 min, and finally kept at 1150°C for 10 min, and finally naturally cooled to obtain uniformly foamed high-strength ceramsite.

[0035] Example 2

[0036] The preparation method of the high-strength ceramsite of the present embodiment comprises the following steps:

[0037] (1) secondary aluminum ash, electroplating sludge and construction sludge after drying and grinding are sieved to make their particle sizes less than 150 μm, and then 50 parts of secondary aluminum ash, 40 parts of electroplating sludge and 10 parts of construction sludge are mixed evenly, sprayed with water and continuously stirred, and pressed into cylindrical blanks by a manual press at a pressure of 4 MPa, and naturally air-dried for 24 hours; the secondary aluminum ash includes the following components in weight percentage: 6.79% SiO2, 8.15% Al2O3, 2.07% Fe2O3, 2.07% CaO, 4.81% MgO, 0.11% Cu, 0.02% Ni, 0.08% Cr, 0.25% Zn, and 0.007% Pb;

[0038] (2) The naturally air-dried cylindrical blank was first kept at 780°C for 30 min, then kept at 1100°C for 15 min, and finally kept at 1180°C for 10 min, and finally cooled naturally.

[0039] Example 3

[0040] The difference between this embodiment and embodiment 1 is that in step (1), secondary aluminum ash, electroplating sludge and construction sludge after drying and grinding are sieved to make their particle sizes less than 150 μm, 40 parts of secondary aluminum ash, 20 parts of electroplating sludge and 40 parts of construction sludge are evenly mixed, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0041] Example 4

[0042] The difference between this embodiment and embodiment 1 is that in step (1), secondary aluminum ash, dried and ground electroplating sludge and construction sludge are sieved to make their particle sizes less than 150 μm, 40 parts of secondary aluminum ash, 10 parts of electroplating sludge and 50 parts of construction sludge are evenly mixed, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0043] Example 5

[0044] The difference between this embodiment and embodiment 1 is that in step (1), secondary aluminum ash, electroplating sludge and construction sludge after drying and grinding are sieved to make their particle sizes less than 150 μm, 30 parts of secondary aluminum ash, 20 parts of electroplating sludge and 50 parts of construction sludge are evenly mixed, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0045] Comparative Example 1

[0046] The difference between this comparative example and Example 1 is that in step (1), secondary aluminum ash, dried and ground electroplating sludge and construction sludge are sieved to make their particle sizes less than 150 μm, 20 parts of secondary aluminum ash, 20 parts of electroplating sludge and 50 parts of construction sludge are evenly mixed, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0047] Comparative Example 2

[0048] The difference between this comparative example and Example 1 is that in step (1), secondary aluminum ash, dried and ground electroplating sludge and construction sludge are sieved to make their particle sizes less than 150 μm, and then 70 parts of secondary aluminum ash, 20 parts of electroplating sludge and 50 parts of construction sludge are evenly mixed, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0049] Comparative Example 3

[0050] The difference between this comparative example and Example 1 is that in step (1), secondary aluminum ash, dried and ground electroplating sludge and construction sludge are sieved to make their particle sizes less than 150 μm, and then 50 parts of secondary aluminum ash, 5 parts of electroplating sludge and 10 parts of construction sludge are mixed evenly, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0051] Comparative Example 4

[0052] The difference between this comparative example and Example 1 is that in step (1), secondary aluminum ash, dried and ground electroplating sludge and construction sludge are sieved to make their particle sizes less than 150 μm, 50 parts of secondary aluminum ash, 45 parts of electroplating sludge and 10 parts of construction sludge are mixed evenly, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0053] Comparative Example 5

[0054] The difference between this comparative example and Example 1 is that in step (1), secondary aluminum ash, dried and ground electroplating sludge and construction sludge are sieved to make their particle sizes less than 150 μm, and then 50 parts of secondary aluminum ash, 40 parts of electroplating sludge and 5 parts of construction sludge are mixed evenly, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0055] Comparative Example 6

[0056] The difference between this comparative example and Example 1 is that in step (1), secondary aluminum ash, dried and ground electroplating sludge and construction sludge are sieved to make their particle sizes less than 150 μm, 50 parts of secondary aluminum ash, 40 parts of electroplating sludge and 65 parts of construction sludge are mixed evenly, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0057] Comparative Example 7

[0058] The difference between this comparative example and Example 1 is that in step (1), the secondary aluminum ash, the electroplating sludge and the construction sludge after drying and grinding are sieved to make their particle sizes less than 150 μm, and then 40 parts of the electroplating sludge and 10 parts of the construction sludge are mixed evenly, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0059] Comparative Example 8

[0060] The difference between this comparative example and Example 1 is that in step (1), secondary aluminum ash, dried and ground electroplating sludge and construction sludge are sieved to make their particle sizes less than 150 μm, 50 parts of secondary aluminum ash and 10 parts of construction sludge are mixed evenly, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0061] Comparative Example 9

[0062] The difference between this comparative example and Example 1 is that in step (1), secondary aluminum ash, dried and ground electroplating sludge and construction sludge are sieved to make their particle sizes less than 150 μm, 50 parts of secondary aluminum ash and 40 parts of electroplating sludge are mixed evenly, sprayed with water and continuously stirred, and pressed into a cylindrical blank at a pressure of 3 MPa using a manual press, and naturally air-dried for 24 hours.

[0063] Table 1 Heavy metal content of high strength ceramsite

[0064] Cu(%) Ni(%) Cr(%) Pb(%) Zn(%) Example 1 0.028 0.002 0.009 0.001 0.033 Example 2 0.046 0.001 0.012 0.001 0.043 Example 3 0.020 0.002 0.013 0.003 0.053 Example 4 0.022 0.001 0.003 0.006 0.037 Example 5 0.023 0.004 0.003 0.003 0.138

[0065] Table 2 Performance data of high strength ceramsite

[0066]

[0067]

[0068] The heavy metal content of the high-strength ceramsite obtained in Examples 1-5 is shown in Table 1, which meets the national standard and has a cylinder pressure strength of ≥5MPa; in Comparative Example 1, a small amount of secondary aluminum ash is used, and the thermal stability of the obtained ceramsite is reduced; in Comparative Example 2, an excessive amount of secondary aluminum ash is used, and more impurities are introduced into the structure of the obtained ceramsite, affecting its performance; in Comparative Example 3, a small amount of electroplating sludge is used, and the strength of the obtained ceramsite product is reduced; in Comparative Example 4, an excessive amount of electroplating sludge is used, and the density and strength of the ceramsite are reduced; in Comparative Example 5, a small amount of construction sludge is used, and the strength of the obtained ceramsite is reduced; in Comparative Example 6, an excessive amount of construction sludge is used, and the density and strength of the ceramsite are reduced; Comparative Example 7 does not use secondary aluminum ash, and the thermal stability and strength of the obtained ceramsite are reduced; Comparative Example 8 does not use electroplating sludge and Comparative Example 9 does not use construction sludge, the eutectic temperature will be higher, the required sintering temperature will increase, and the energy consumption will increase.

[0069] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A high-strength ceramsite, characterized in that: The invention comprises the following raw materials in parts by weight: 30 to 60 parts of secondary aluminum ash, 10 to 40 parts of electroplating sludge and 10 to 60 parts of construction sludge.

2. The high-strength ceramsite according to claim 1, characterized in that The secondary aluminum ash includes the following components in weight percentage: 5-10% SiO2, 5-10% Al2O3, 1-5% Fe2O3, 1-5% CaO, and 3-8% MgO.

3. The high-strength ceramsite according to claim 2, characterized in that: The secondary aluminum ash also includes 0.10-0.40% Cu, 0.01-0.06% Ni, 0.05-0.20% Cr, 0.10-0.50% Zn, and 0.006-0.08% Pb.

4. The high-strength ceramsite according to claim 1, characterized in that The electroplating sludge includes the following components in weight percentage: 1-5% SiO2, 3-8% Al2O3, 8-15% Fe2O3, 20-28% CaO, and 5-10% MgO.

5. The high-strength ceramsite according to claim 4, characterized in that: The electroplating sludge also includes 0.05-0.20% Cu, 0.10-0.20% Ni, 0.15-0.25% Cr, 0.30-0.80% Zn, and 0.01-0.03% Pb.

6. The high-strength ceramsite according to claim 1, characterized in that: Construction sludge includes the following components in weight percentage: 50-60% SiO2, 10-20% Al2O3, 5-10% Fe2O3, and 2-5% MgO.

7. The high-strength ceramsite according to claim 6, characterized in that: Construction sludge also includes 0.002-0.006% Cu, 0.003-0.008% Ni, 0.01-0.03% Cr, 0.01-0.05% Zn, and 0.001-0.005% Pb.

8. The high-strength ceramsite according to claim 1, characterized in that: The content of heavy metals in the high-strength ceramsite is: Cu 0.02-0.05%, Ni 0.001-0.005%, Cr 0.003-0.014%, Zn 0.03-0.17%, Pb 0.001-0.006%.

9. A method for preparing high-strength ceramsite as claimed in claim 1, characterized in that: The following steps are involved: After the secondary aluminum ash, electroplating sludge and construction sludge are evenly mixed, water is sprayed and stirred continuously, pressed and then air-dried, and naturally cooled after high-temperature sintering.

10. The preparation method according to claim 1, characterized in that: Three-stage heat preservation sintering is adopted during high temperature sintering.

Citation Information

Patent Citations

  • Ceramsite foamed in situ by using secondary aluminum ash and preparation method thereof

    CN116606123A

Cited By

  • Method for preparing ceramsite from hazardous waste chromium-containing sludge and secondary aluminum ash and product thereof

    CN120058258A